Dehydrocoupling and Silazane Cleavage Routes to Organic–Inorganic Hybrid Polymers with NBN Units in the Main Chain. Issue 25 (6th May 2016) - Lorenz, Thomas; Lik, Artur; Plamper, Felix A.; Helten, Holger
Abstract: Despite the great potential of both π‐conjugated organoboron polymers and BN‐doped polycyclic aromatic hydrocarbons in organic optoelectronics, our knowledge of conjugated polymers with B−N bonds in their main chain is currently scarce. Herein, the first examples of a new class of organic–inorganic hybrid polymers are presented, which consist of alternating NBN and para‐phenylene units. Polycondensation with B−N bond formation provides facile access to soluble materials under mild conditions. The photophysical data for the polymer and molecular model systems of different chain lengths reveal a low extent of π‐conjugation across the NBN units, which is supported by DFT calculations. The applicability of the new polymers as macromolecular polyligands is demonstrated by a cross‐linking reaction with Zr IV . Abstract : Polymerization through B−N bond formation provides facile access to the first derivatives of a new class of organic–inorganic hybrid polymers, which show some π‐conjugation across the NBN units. Cross‐linking with Zr IV demonstrates the applicability of these materials as macromolecular polyligand systems. Mes=2, 4, 6‐trimethylphenyl.